Struktur Topik-Komen dalam Lirik Lagu Shounen to Mahou no Robotto - Ilham Hijrah Mustaqim; Ypsi Soeria Soemantri; Puspa Mirani Kadir; Wagiati Wagiati (Chi'e: Journal of Japanese Learning and Teaching, 2022)
This study aims to describe the topic-comment structure in the discourse of the lyrics of the song Shounen to Mahou no Robotto. The method used in data collection is the free-to-talk method, while for the study of data, the method used is the distributional method. The data is taken from the discourse of the lyrics of the song Shounen to Mahou no Robotto. A distributional study method is used at the data analysis stage, which uses a determining tool for language elements. From the results of the research, most of the topics found in the form of subjects that were topicalized with the topic particle marker wa, but topics can also be stated by moving elements that are not subjected to the beginning of the sentence, even though the particle wa does not mark them. Topicalization can occur in single or compound sentences. In compound sentences, the same topic can be used in both clauses, or the two clauses can have different topics. This study found more topicalization data without wa particle markers than previous studies, indicating the characteristics of song lyrics data that used language more flexibly than written data sources. Keywords : Jurnal Pendidikan Bahasa Jepang Japanese Education JournalDiscourse AnalysisJapanese Discourse